Efficiency of educational services in the city of Chamchamal: (A study in the geography of services) (Raparin Journal of Humanities (RJH), 2023)
Education is one of the most important sectors of any state, or a region the vital role it has in enhancing the cultural level of a society and developing their scientific state by committing to the educational standards and the effective distribution of educational services in populated areas.The city of Chamachamal، similar to other cities of the world in general and other cities of Kurdistan in particular، is not deprived from educational services، which is, however, not up to the growing number of the resident. Generally، the educational services include these stages: Kindergarten, basic education (primary and intermediate 1-9), and secondary education (10-12).This study aims to identify the educational services in the city of Chamchaml and delimit their shortcomings using the Geographic Information System (GIS) to display   the way each of the educational services in the city’s neighborhoods. The current study has been based on data and information presented by the directorate of education of Chamchamal. To enrich the study via gaining first hand details, field visits were paid to the kindergartens and schools of Chamchamal for the academic year (2020-2021).